Bortezomib-Based Regimens for Newly Diagnosed Multiple Myeloma in China: A Report of 12-Year Real-World Data - He, Jingsong; He, Donghua; Han, Xiaoyan; Zheng, Gaofeng; Wei, Guoqing; Zhao, Yi; Yang, Yang; Wu, Wenjun; Fu, Jiaping; Shou, Lihong; Kong, Hongwei; Huang, He; et al. (Frontiers in Pharmacology, 2020)
Background: Improve the treatment quality might affect patients’ efficacy and survival. Methods: 530 multiple myeloma patients treated in 4 hematological centers in China from February 2006 to August 2018 were enrolled. General characteristics, treatment regimens and cycles, efficacy, survival and adverse events of the patients treated before and after August 2013 (later refer to as the before-2013 and after-2013 group) were analysed and compared. Results: The results suggested that patients who received optimized treatment regimen and route of administration completed more cycles of treatment in the after-2013 group. Although the overall response rate was similar between the two groups (88.6% vs 90.5%), patients in the after-2013 group had higher complete remission rate (39.1% vs 28.6%) and better progression-free survival. Subgroup analysis suggested that patients aged 65 years and older, with non-high-risk D-S, ISS, and R-ISS stages, had a significant benefit in progression-free survival. Conclusion: Therefore, in clinical practice in China, by reducing the economic burden brought by the treatment on patients and optimizing the treatment regimen, more patients can be treated with better regimens in a prolonged duration to achieve better efficacy and survival, especially in elderly and non-high-risk patients.